Improvement of Homogeneity and Aspect Ratio of Silicon Tips for Field Emission by Reactive-Ion Etching. (6th April 2014) - Lawrowski, Robert Damian; Prommesberger, Christian; Langer, Christoph; Dams, Florian; Schreiner, Rupert
Abstract : The homogeneity of emitters is very important for the performance of field emission (FE) devices. Reactive-ion etching (RIE) and oxidation have significant influences on the geometry of silicon tips. The RIE influences mainly the anisotropy of the emitters. Pressure has a strong impact on the anisotropic factor. Reducing the pressure results in a higher anisotropy, but the etch rate is also lower. A longer time of etching compensates this effect. Furthermore an improvement of homogeneity was observed. The impact of uprating is quite low for the anisotropic factor, but significant for the homogeneity. At low power the height and undercut of the emitters are more constant over the whole wafer. The oxidation itself is very homogeneous and has no observable effect on further variation of the homogeneity. This modified fabrication process allows solving the problem of inhomogeneity of previous field emission arrays.